News Media Coverage of the Vice-Presidential Selection Process - Devine, Christopher J. author. (orcid)0000-0003-2445-9775 Link aut Link
XIX, 137 p. 3 illus., 2 illus. in color.
Keywords: “In this important volume, Devine examines how the media describe potential candidates when covering the ‘veepstakes,’ and he insightfully critiques the media’s relative focus on electoral versus governing considerations.” —Herbert F. Weisberg, Professor Emeritus of Political Science, The Ohio State University, USA “Well-written and full of fascinating details…. I loved this book and learned a lot from it. I couldn’t put it down until I finished it.” —Karine Prémont, Professor of Political Science, University of Sherbrooke and Deputy Director, Center for United States Studies, University of Québec, Montréal, Canada “A must-read for anyone who is interested in developing a greater understanding of political media coverage, vice-presidential selection, and American electoral politics.” —Andrew D. Green, Behavioral Sciences Department Chair and Professor of Political Science, Central College, USA This book provides the first systematic, empirical analysis of the media’s approach to US vice-presidential selection (or the “veepstakes”). In their news coverage, Devine finds that media outlets typically treat vice-presidential selection as little more than a game—by focusing on how potential running mates might help to win the election, rather than how they might help the next president to govern. Based on an original content analysis of hundreds of veepstakes profiles from 2000–2020, this book quantifies the news media’s relative emphasis on various selection criteria, in general and across different electoral circumstances. The analysis suggests that journalists generally fail to serve the public interest by emphasizing electoral over governing considerations. However, Devine also points to positive examples of media coverage that help the public to evaluate potential running mates’ governing credentials, and suggests ways in which scholars, journalists, and citizens might encourage media outlets toprovide more substantive, responsible coverage of the vice-presidential selection process in future elections. Christopher J. Devine is Associate Professor of Political Science at the University of Dayton, USA. His previous books include Do Running Mates Matter? The Influence of Vice Presidential Candidates in Presidential Elections (2020).